Sheet for workpiece processing and method for manufacturing same
By using solvent-free acrylic adhesive containing a blocker, the problem of high environmental load on the adhesive layer in the workpiece processing sheet is solved, and the application period of the adhesive layer is extended and the surface property is improved.
Patent Information
- Application Number
- CN202380053675.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-02
- Filing Date
- 2023-10-25
- Publication Date
- 2025-03-04
AI Technical Summary
The adhesive layer in the existing workpiece processing sheet is prepared with an organic solvent, and the application period of the solvent-free adhesive is short, resulting in poor surface properties of the adhesive layer.
A solvent-free acrylic adhesive containing a blocker for delaying crosslinking reaction is used to form an adhesive layer through the coating and heating process, extending the applicable period and reducing environmental load.
The environmental load is reduced and the solvent-free adhesive composition has a sufficient applicable life, and the formed adhesive layer has excellent surface properties.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to a workpiece processing sheet which can be used for processing a workpiece such as a semiconductor wafer. Background Art
[0002] Semiconductor wafers such as silicon and gallium arsenide, various packages, etc. are manufactured in a large diameter state, and after being cut (diced) into chips and peeled (picked up), they are transferred to the mounting process as the next process. At this time, the workpiece such as the semiconductor wafer is stacked on an adhesive sheet having a base material and an adhesive layer (hereinafter, sometimes referred to as a "workpiece processing sheet"), and is processed by back grinding, dicing, cleaning, drying, expanding, picking up, mounting, etc.
[0003] As the workpiece processing sheet, there is a sheet formed using an adhesive composition containing an acrylic copolymer produced by a solution polymerization method (for example, Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-106283 Summary of the invention
[0007] 1. Technical issues to be resolved
[0008] In recent years, there has been an increasing demand for reducing environmental load in various technical fields. This also applies to technical fields related to workpiece processing sheets, for example, where it is required to reduce components that have an impact on the environment as much as possible.
[0009] Here, in the workpiece processing sheet disclosed in Patent Document 1, since an acrylic copolymer prepared by solution polymerization is used during its manufacture, the adhesive layer contains a predetermined amount of organic solvent. Such organic solvents usually have an impact on the environment, so it is desired to reduce their content as much as possible.
[0010] From this perspective, the use of acrylic adhesives formed without using organic solvents is being studied to form an adhesive layer of a workpiece processing sheet. However, such solvent-free adhesives have the problem that the pot life (referring to the time from the state of mixing for coating to the state of being able to be used for coating, also referred to as the "usable period") of the coating liquid used to form the adhesive is often shortened. That is, when forming the adhesive layer, the coating liquid is easy to solidify, and as a result, as expected, it is easy to cause problems such as being unable to be coated or having poor surface properties of the formed adhesive layer.
[0011] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide a workpiece processing sheet that can reduce environmental load and in which an adhesive composition for forming an adhesive layer has a sufficient pot life.
[0012] (II) Technical solution
[0013] In order to achieve the above-mentioned purpose, first, the present invention provides a workpiece processing sheet, which is a workpiece processing sheet comprising a substrate and an adhesive layer laminated on one side of the substrate, characterized in that the adhesive layer is composed of an acrylic adhesive, and the acrylic adhesive is formed from a solvent-free adhesive composition containing a retardant that delays a cross-linking reaction (Invention 1).
[0014] The workpiece processing sheet of the above invention (Invention 1) is formed by using the solventless adhesive composition containing the retarder as the adhesive layer, thereby effectively reducing environmental load, and the solventless adhesive composition has a sufficient pot life, and the formed adhesive layer exhibits excellent performance.
[0015] In the above invention (Invention 1), it is preferred that the solvent-free adhesive composition contains an acrylic oligomer (Invention 2).
[0016] In the above invention (Invention 1), it is preferred that the weight average molecular weight of the acrylic oligomer is 1,000 or more and 40,000 or less (Invention 3).
[0017] In the above invention (Invention 1), it is preferred that the retardant is a compound having a diketone skeleton (Invention 4).
[0018] In the above invention (Invention 1), it is preferred that the content of the retarder in the solvent-free adhesive composition is 2 mass % or more and 30 mass % or less (Invention 5).
[0019] In the above invention (Invention 1), it is preferred that the solvent-free adhesive composition contains a crosslinking agent (Invention 6).
[0020] In the above invention (Invention 1), the solvent-free adhesive composition preferably contains a catalyst for accelerating the cross-linking reaction (Invention 7).
[0021] Second, the present invention provides a manufacturing method, which is a manufacturing method for the workpiece processing sheet (Invention 1), characterized in that the manufacturing method includes: a coating step, coating the solvent-free adhesive composition on one side of the substrate or process sheet to form a coating film; and a heating step, heating the coating film to form the adhesive layer formed by curing the coating film (Invention 8).
[0022] (III) Beneficial effects
[0023] The workpiece processing sheet of the present invention can reduce environmental load, and the adhesive composition used to form the adhesive layer has a sufficient pot life. DETAILED DESCRIPTION
[0024] Hereinafter, embodiments of the present invention are described.
[0025] The workpiece processing sheet of this embodiment comprises a substrate and an adhesive layer laminated on one side of the substrate, and the adhesive layer is composed of an acrylic adhesive formed of a solvent-free adhesive composition containing a retarder for delaying a crosslinking reaction.
[0026] Since the workpiece processing sheet of the present embodiment does not substantially contain an organic solvent in the solvent-free adhesive composition for forming the adhesive layer, the environmental load can be well reduced by using the workpiece processing sheet of the present embodiment. Here, the so-called "substantially does not contain an organic solvent" means that the content of the organic solvent in the adhesive layer is 1% by mass or less, and particularly refers to a content of 0.5% by mass or less. In addition, the content of the volatile component in the adhesive layer is preferably 2.5% by mass or less, and particularly preferably 1.8% by mass or less.
[0027] In addition, in the workpiece processing sheet of the present embodiment, the solvent-free adhesive composition contains a retarder, which can appropriately inhibit the curing of the composition and have a sufficient pot life. Thus, when manufacturing the workpiece processing sheet of the present embodiment, the solvent-free adhesive composition can be applied in a uniform thickness, and the generation of stripes on the surface of the formed adhesive layer can be well inhibited.
[0028] 1. Composition of workpiece processing sheets
[0029] (1) Base material
[0030] As the substrate of the present embodiment, as long as the desired function is exerted when using the workpiece processing sheet, it is not particularly limited. In particular, the substrate is preferably a resin film with a resin-based material as the main material. As a specific example, polyolefin films such as polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, ethylene-norbornene copolymer film, and norbornene resin film can be cited; polyester films such as polyethylene terephthalate film, polybutylene terephthalate film, and polyethylene naphthalate; ethylene-vinyl acetate copolymer film; ethylene-(methyl) acrylic acid copolymer film, ethylene-(methyl) methyl acrylate copolymer film, and other ethylene-(methyl) acrylic acid ester copolymer films and other ethylene-(methyl) acrylic acid ester copolymer films; polyvinyl chloride films such as polyvinyl chloride film and vinyl chloride copolymer film; (methyl) acrylic acid ester copolymer film; polyurethane film; polyimide film; polystyrene film; polycarbonate film; fluororesin film, etc. In addition, modified films such as cross-linked films and ionomer films of these components can also be used. In addition, the substrate can also be a laminated film formed by laminating multiple layers of the film. In the laminated film, the materials constituting each layer can be of the same type or of different types. Among them, it is preferred to use a polyester film (especially a polyethylene terephthalate film) as the substrate. In addition, in this specification, the so-called "(meth) acrylic acid" refers to both acrylic acid and methacrylic acid. The same is true for other similar terms. In addition, the "polymer" in this specification also includes the concept of "copolymer".
[0031] The substrate may contain various additives such as flame retardants, plasticizers, antistatic agents, lubricants, antioxidants, colorants, infrared absorbers, ultraviolet absorbers, ion traps, etc. The content of these additives is not particularly limited, but is preferably within a range in which the substrate can exert the desired function.
[0032] In order to improve the adhesion with the adhesive layer, the surface of the substrate on which the adhesive layer is to be laminated may be subjected to a surface treatment such as primer treatment, corona treatment, or plasma treatment.
[0033] The thickness of the substrate can be appropriately set according to the method of using the workpiece processing sheet, and is, for example, preferably 200 μm or less, particularly preferably 150 μm or less. In addition, the thickness of the substrate is preferably 10 μm or more, particularly preferably 25 μm or more.
[0034] (2)Adhesive layer
[0035] As mentioned above, the adhesive layer of the present embodiment is composed of an acrylic adhesive, and the acrylic adhesive is formed by a solvent-free adhesive composition containing a retarder that delays the crosslinking reaction. As the component except the retarder included in the adhesive composition, as long as the adhesive layer consisting of the acrylic adhesive can be formed, there is no particular limitation. From the perspective of easily forming an adhesive layer well, preferably, except the retarder, the solvent-free adhesive composition also contains an acrylic oligomer, a crosslinking agent and a catalyst. In this case, by the effect of the catalyst contained in the solvent-free adhesive composition, the acrylic oligomer is crosslinked by the crosslinking agent to form an adhesive layer. And the retarder appropriately delays the crosslinking reaction, thus appropriately prolonging the pot life of the solvent-free adhesive composition.
[0036] (2-1) Acrylic polymer
[0037] As the acrylic oligomer, there is no particular limitation as long as it contains an acrylic monomer as a monomer constituting the oligomer and can undergo the cross-linking reaction, and known substances can be used. As the acrylic oligomer, for example, an oligomer formed by one or more acrylic monomers, or an oligomer formed by one or more acrylic monomers and a monomer other than an acrylic monomer can be used. In addition, the solvent-free adhesive composition can contain only one acrylic oligomer, or can contain multiple acrylic oligomers.
[0038] The weight average molecular weight of acrylic acid oligomer is preferably 40,000 or less, particularly preferably 25,000 or less, and further preferably 18,000 or less. By having a weight average molecular weight of 40,000 or less, the viscosity of the solvent-free adhesive composition (coating liquid) can be suppressed to be too high, and an adhesive layer with a more excellent surface state can be easily formed. In addition, the weight average molecular weight is preferably 1,000 or more, particularly preferably 1,500 or more, and further preferably 2,500 or more. By having a weight average molecular weight of 1,000 or more, the adhesive layer formed has sufficient cohesive force, and it is easy to exert the strength, adhesion, etc. required as an adhesive layer.
[0039] From the viewpoint of being able to carry out the crosslinking reaction well, the acrylic oligomer preferably has a reactive group that can serve as a crosslinking point for the crosslinking reaction. Examples of the reactive group include hydroxyl group, carboxyl group, amino group, epoxy group, alkoxy group and the like.
[0040] Furthermore, the acrylic oligomer also preferably contains a monomer having the above-mentioned reactive group as a monomer unit constituting the oligomer. In particular, the acrylic oligomer preferably contains a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer).
[0041] Examples of the hydroxyl-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. These monomers may be used alone or in combination of two or more.
[0042] When the acrylic acid oligomer has a hydroxyl group, the hydroxyl value of the acrylic acid oligomer is preferably more than 20 mgKOH / g, particularly preferably more than 30 mgKOH / g, and more preferably more than 100 mgKOH / g. The hydroxyl value of the acrylic acid oligomer is more than 20 mgKOH / g, and the acrylic acid oligomer has enough crosslinking points and is easy to have a good crosslinking reaction. In addition, the hydroxyl value of the acrylic acid oligomer is preferably less than 170 mgKOH / g. The hydroxyl value of the acrylic acid oligomer is less than 170 mgKOH / g, which is easy to suppress the crosslinking reaction of the acrylic acid oligomer from being excessively carried out, and it is easy to reach a suitable pot life of the solvent-free adhesive composition (coating liquid).
[0043] (2-2) Blockers
[0044] The retardant is not limited as long as it can retard the crosslinking reaction of the solvent-free adhesive composition, but a compound having a diketone skeleton is preferred from the viewpoint of easily causing appropriate retardation.
[0045] A diketone skeleton refers to a skeleton formed by connecting two ketone groups via carbon atoms. Examples of compounds having a diketone skeleton include β-diketones, β-diesters, and the like, and specifically, acetylacetone (acac), 2-acetoacetoxyethyl methacrylate (AAEM), methyl acetoacetate, ethyl acetoacetate, n-propyl acetoacetate, isopropyl acetoacetate, malonic acid esters, and the like. Among them, β-diketones are preferably used, and specifically, at least one of acetylacetone and 2-acetoacetoxyethyl methacrylate is preferably used.
[0046] The content of the retarder in the solvent-free adhesive composition is preferably more than 2% by mass, and more than 6% by mass is particularly preferred. By having a content of more than 2% by mass, the solvent-free adhesive composition (coating liquid) is easy to have a moderate pot life. In addition, the content of the retarder is preferably less than 30% by mass, and more preferably less than 18% by mass. By having a content of less than 30% by mass, it is easy to carry out a cross-linking reaction well, and it is easy to form a fully cured adhesive layer.
[0047] (2-3) Cross-linking agent
[0048] The crosslinking agent is not particularly limited as long as it can crosslink the acrylic oligomer, and a known crosslinking agent can be used. In particular, as long as the acrylic oligomer has the above-mentioned reactive group, a crosslinking agent that can react with the reactive group is preferred.
[0049] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. The crosslinking agent may be used alone or in combination of two or more.
[0050] Here, when the acrylic oligomer has a hydroxyl group as the reactive group, it is preferable to use an isocyanate crosslinking agent having excellent reactivity with the hydroxyl group as the crosslinking agent.
[0051] The isocyanate crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as pentamethylene diisocyanate and hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and biuret forms, isocyanurate forms, allophanate forms thereof, and adducts thereof as reactants with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil.
[0052] Among them, from the perspective of easily and effectively extending the pot life, isocyanurate or allophanate of aliphatic polyisocyanate is preferred, and at least one of pentamethylene diisocyanate isocyanurate, hexamethylene diisocyanate isocyanurate and hexamethylene diisocyanate isocyanurate is particularly preferred.
[0053] The content of the crosslinking agent in the solvent-free adhesive composition is preferably more than 10 mass %, particularly preferably more than 15 mass %. By the content of the crosslinking agent is more than 10 mass %, it is easy to carry out crosslinking reaction well, and it is easy to form the adhesive layer after fully solidification. In addition, the content of the crosslinking agent is preferably less than 50 mass %, particularly preferably less than 40 mass %. By the content of the crosslinking agent is less than 50 mass %, the solvent-free adhesive composition (coating liquid) is easy to have a moderate pot life.
[0054] (2-4) Catalyst
[0055] As the catalyst, there is no particular limitation as long as it can promote the crosslinking reaction of the acrylic oligomer and the crosslinking agent, and a known catalyst can be used. From the perspective of being able to effectively promote the crosslinking reaction, an organometallic compound is preferably used as the catalyst. Examples of the organometallic compound include organotitanium compounds, organotin compounds, organozirconium compounds, organobismuth compounds, organolead compounds, organozinc compounds, etc., among which organotitanium compounds are preferably used.
[0056] Examples of the organic titanium compound include titanium tetra-2-ethylhexoxide and titanium tetra-n-butoxide. Among them, titanium tetra-2-ethylhexoxide is preferably used.
[0057] The content of the catalyst in the solvent-free adhesive composition is preferably more than 0.05 mass %, particularly preferably more than 0.1 mass %, more preferably more than 0.2 mass %. By the content of catalyst is more than 0.05 mass %, it is easy to carry out cross-linking reaction well, and it is easy to form the adhesive layer after fully solidified. In addition, the content of catalyst is preferably less than 4 mass %, particularly preferably less than 2 mass %, more preferably less than 0.5 mass %. By the content of catalyst is less than 4 mass %, solvent-free adhesive composition (coating liquid) is easy to have appropriate pot life.
[0058] (2-5) Other ingredients
[0059] As long as the effects brought about by the workpiece processing sheet of this embodiment are not impaired, the solvent-free adhesive composition of this embodiment can be added with desired additives, such as silane coupling agents, antistatic agents, tackifiers, antioxidants, light stabilizers, softeners, fillers, refractive index adjusters, etc.
[0060] (2-6) Preparation of solvent-free adhesive composition
[0061] The solvent-free adhesive composition of the present embodiment can be produced by mixing the retarder with other components (particularly, an acrylic oligomer, a crosslinking agent, and a catalyst), and adding additives as needed.
[0062] In addition, since the solvent-free adhesive composition of the present embodiment is solvent-free, it has a moderate viscosity mainly due to the polymerized component. Therefore, the solvent-free adhesive composition of the present embodiment can be used directly as a coating liquid without adding a diluent or the like.
[0063] (2-7) Gel fraction
[0064] The gel fraction of the adhesive layer in the present embodiment is preferably 50% or more, particularly preferably 70% or more, and more preferably 80% or more. By having a gel fraction of 50% or more of the above-mentioned adhesive, the cohesive force of the adhesive is improved, and it is easy to have the durability required as a workpiece processing sheet. In addition, the gel fraction of the adhesive layer is preferably 100% or less, particularly preferably 98% or less, and more preferably 95% or less. By having a gel fraction of 100% or less of the adhesive layer, the adhesive will not harden too much and is easy to exert the desired adhesive force. In addition, the details of the method for determining the gel rate of the adhesive layer are described in the test examples described later.
[0065] (2-8) Thickness of adhesive layer
[0066] The thickness of the adhesive layer in this embodiment is preferably 1 μm or more, particularly preferably 3 μm or more, and more preferably 5 μm or more. In addition, the thickness of the adhesive layer is preferably 100 μm or less, particularly preferably 80 μm or less, and more preferably 60 μm or less. By the thickness of the adhesive layer being within the above range, the workpiece processing sheet of this embodiment is easy to exert the desired adhesion.
[0067] (3) Peel sheet
[0068] In the workpiece processing sheet of the present embodiment, a release sheet may be laminated on the surface of the adhesive layer opposite to the substrate (hereinafter sometimes referred to as "adhesive surface") before being attached to the workpiece to protect the surface.
[0069] The composition of the release sheet is optional, and examples thereof include a sheet obtained by subjecting a plastic film to a release treatment using a release agent or the like. Specific examples of the plastic film include polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; and polyolefin films such as polypropylene and polyethylene. As the release agent, silicone-based, fluorine-based, and long-chain alkyl-based films can be used, and silicone-based films are preferred because they are inexpensive and can provide stable performance.
[0070] The thickness of the release sheet is not particularly limited, and may be, for example, 20 μm or more and 250 μm or less.
[0071] (4) Others
[0072] In the workpiece processing sheet of the present embodiment, an adhesive layer can be stacked on the surface of the adhesive layer on the opposite side to the substrate. At this time, the workpiece processing sheet of the present embodiment can be used as a cutting and solidifying chip. In this sheet, by attaching a workpiece on the surface of the adhesive layer on the opposite side to the adhesive layer, the adhesive layer is cut together with the workpiece, thereby obtaining a chip stacked with a singulated adhesive layer. Through the singulated adhesive layer, the chip can be easily fixed on the object carrying the chip. As the material constituting the adhesive layer, it is preferred to use a material containing a thermoplastic resin and a low molecular weight thermosetting adhesive component, a material containing a B-stage (semi-cured) thermosetting adhesive component, etc.
[0073] In addition, in the workpiece processing sheet of the present embodiment, a protective film forming layer can also be stacked on the adhesive surface of the adhesive layer. In this case, the workpiece processing sheet of the present embodiment can be used as a protective film forming and cutting sheet. In this sheet, by attaching the workpiece to the surface of the protective film forming layer on the opposite side to the adhesive layer, the protective film forming layer is cut together with the workpiece, thereby obtaining a chip stacked with a singulated protective film forming layer. As the workpiece, it is preferred to use a workpiece with a circuit formed on a single surface, in which case the protective film forming layer is usually stacked on the surface opposite to the surface on which the circuit is formed. By curing the singulated protective film forming layer at a specified time, a protective film with sufficient durability can be formed on the chip. The protective film forming layer is preferably composed of an uncured curable adhesive.
[0074] 2. Method for manufacturing sheet for workpiece processing
[0075] The manufacturing method of the workpiece processing sheet of the present embodiment is not particularly limited. Preferably, the workpiece processing sheet of the present embodiment is manufactured by a method including the following steps: a coating step, coating the solvent-free adhesive composition on one side of a substrate or a process sheet to form a coating film; and a heating step, heating the coating film to form an adhesive layer formed by curing the coating film.
[0076] The coating in the coating step can be performed by a known method, for example, a rod coating method, a doctor blade coating method, a shaft coating method, a blade coating method, a die coating method, a gravure coating method, etc. In addition, the coating liquid of the solvent-free adhesive composition is not particularly limited in properties as long as it can be coated, and sometimes contains a component for forming an adhesive layer as a solute, and sometimes contains a component for forming an adhesive layer as a dispersoid.
[0077] When the solvent-free adhesive composition is applied to a substrate, an adhesive layer is directly formed on the substrate by a subsequent heating process, thereby obtaining a workpiece processing sheet having a substrate and an adhesive layer. On the other hand, when the solvent-free adhesive composition is applied to a process sheet, an adhesive layer is formed on the process sheet by a subsequent heating process, and then a single surface of the substrate is laminated on the surface of the adhesive layer on the opposite side to the process sheet, thereby obtaining a workpiece processing sheet. As the process sheet, the peeling sheet described above can be used.
[0078] In the heating process, the cross-linking reaction of the solvent-free adhesive composition is carried out well by heating, so that the coating is fully cured to form an adhesive layer. The heating temperature is preferably above 95°C, more preferably above 100°C, particularly preferably above 105°C, and more preferably above 110°C. In addition, the temperature is preferably below 150°C, particularly preferably below 145°C, and more preferably below 140°C. The heating time is preferably more than 1 minute, particularly preferably more than 1.5 minutes, and more preferably more than 2 minutes. In addition, the heating time is preferably less than 6 minutes, particularly preferably less than 5 minutes, and more preferably less than 4.5 minutes. In addition, in order to fully carry out the above-mentioned cross-linking reaction, after the adhesive layer is laminated to the substrate, for example, it can be left to mature for several days in an environment of 23°C and a relative humidity of 50%.
[0079] In addition, in the workpiece processing sheet of the present embodiment, since the adhesive layer is sufficiently cured by the above-mentioned heating, it is not necessary to irradiate active energy such as ultraviolet rays.
[0080] 3. How to use the workpiece processing sheet
[0081] The workpiece processing sheet of this embodiment can be used for processing workpieces such as semiconductor wafers. That is, after the adhesive surface of the workpiece processing sheet of this embodiment is attached to the workpiece, the workpiece can be processed on the workpiece processing sheet. According to the processing, the workpiece processing sheet of this embodiment can be used as a back grinding sheet, a cutting sheet, an expansion sheet, a pick-up sheet, etc. Here, as examples of workpieces, semiconductor components such as semiconductor wafers and semiconductor packages; glass components such as glass plates can be listed.
[0082] In addition, when the workpiece processing sheet of the present embodiment has the above-mentioned adhesive layer, the workpiece processing sheet can be used as a cutting cutting and solidifying wafer. In addition, when the workpiece processing sheet of the present embodiment has the above-mentioned protective film forming layer, the workpiece processing sheet can be used as a protective film forming and cutting sheet.
[0083] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above embodiments also includes all design changes or equivalents within the technical scope of the present invention.
[0084] For example, another layer may be laminated between the substrate and the adhesive layer in the workpiece processing sheet of the present embodiment, or on the surface of the substrate opposite to the adhesive layer.
[0085] Example
[0086] Hereinafter, the present invention will be described in more detail using examples, but the scope of the present invention is not limited to these examples and the like.
[0087] [Example 1]
[0088] (1) Preparation of solvent-free adhesive composition
[0089] To 100 parts by mass (solid content conversion value, the same applies hereinafter) of an acrylic oligomer (manufactured by TOAGOSEI Co., Ltd., product name "ARUFON UH-2041", weight average molecular weight: 2,500, hydroxyl value: 120 mgKOH / g, viscosity at 25° C.: 12,000 mPa·s, glass transition temperature: −50° C.), 3.00 parts by mass of acetylacetone (acac) (manufactured by FUJIFILM Wako Pure Chemical Corporation, product name “ACETYLACETONE”) as a retarder, 30 parts by mass of pentamethylene diisocyanate-based isocyanurate (manufactured by Mitsui Chemicals, Inc., product name “STABiO D-370N”) as a crosslinking agent, and 0.50 parts by mass of tetra-2-ethylhexyl titanium (organic titanium compound, manufactured by Matsumoto Fine Chemical Co., Ltd., product name “ORGATIX TA-30")) was added and mixed thoroughly to obtain a coating liquid (solid content concentration: 100% by mass) of a solvent-free adhesive composition.
[0090] (2) Formation of Adhesive Layer
[0091] The release surface of a release sheet (manufactured by LINTEC CORPORATION, product name "SP-PET381031") in which a silicone release agent layer is formed on one side of a polyethylene terephthalate film having a thickness of 38 μm was coated with a coating liquid of the adhesive composition obtained in the above step (1) at a coating speed of 1 m / min using a roll knife coater, and heated at 130° C. for 2 minutes, thereby obtaining a laminate in which a 25 μm thick adhesive layer was formed on the release sheet.
[0092] (3) Production of workpiece processing sheets
[0093] The adhesive layer side surface of the laminate obtained in the above step (2) was bonded to the adhesive coated surface of an adhesively coated polyethylene terephthalate sheet (manufactured by Mitsubishi Chemical Corporation, thickness: 100 μm) as a substrate to obtain a workpiece processing sheet.
[0094] [Examples 2 to 10]
[0095] Except having changed the composition of the solvent-free adhesive composition as described in Table 1, it carried out similarly to Example 1, and produced the sheet for workpiece processing.
[0096] [Comparative Example 1]
[0097] 100 parts by mass (solid content conversion value, the same applies hereinafter) of an acrylic oligomer (manufactured by TOAGOSEI Co., Ltd., product name "ARUFON UH-2041", weight average molecular weight: 2,500, hydroxyl value: 120 mgKOH / g, viscosity at 25°C: 12,000 mPa·s, glass transition temperature: -50°C), 5 parts by mass of trimethylolpropane-modified toluene diisocyanate (manufactured by TOYOCHEM CO., LTD., product name "TAKENATE D-101E") as a crosslinking agent, 3.00 parts by mass of acetylacetone (acac) (manufactured by FUJIFILM Wako Pure Chemical Corporation, product name "ACETYLACETONE") as a retarder, 0.50 parts by mass of tetra-2-ethylhexyl titanium (organic titanium compound, manufactured by Matsumoto Fine Chemical Co., Ltd., product name "ORGATIX") as a catalyst were mixed. TA-30") was fully mixed with 242.70 parts by mass of methyl ethyl ketone as an organic solvent to obtain a coating liquid of an adhesive composition (solid content concentration: 30% by mass). A workpiece processing sheet was manufactured in the same manner as in Example 1 except that the adhesive layer was formed using the coating liquid.
[0098] [Comparative Example 2]
[0099] A workpiece processing sheet was produced in the same manner as in Comparative Example 1 except that 2-acetoacetoxyethyl methacrylate (AAEM) (manufactured by Mitsubishi Chemical Corporation) was used as a retarder.
[0100] [Comparative Example 3]
[0101] A workpiece processing sheet was produced in the same manner as in Comparative Example 1 except that no retarder was used.
[0102] [Test Example 1] (Evaluation of volatility of organic solvents)
[0103] When manufacturing the workpiece processing sheets of the examples and comparative examples, it was confirmed whether the organic solvent volatilized when the coating film of the adhesive composition was heated and dried on the release sheet. Then, the volatility of the organic solvent was evaluated based on the following criteria. The results are shown in Table 1.
[0104] ○: The organic solvent did not volatilize.
[0105] ×: The organic solvent evaporates.
[0106] [Test Example 2] (Evaluation of odor)
[0107] The distance from the blocker to the nose was set to 10 cm for the blocker used in the examples and comparative examples, and the odor was confirmed by fanning with the hand. Then, the odor of the blocker was evaluated based on the following criteria. The results are shown in Table 1.
[0108] ○: Almost no irritating odor or foul smell was detected.
[0109] △: A slightly irritating odor or a foul odor is detected.
[0110] ×: A pungent odor or a foul odor is strongly felt.
[0111] [Test Example 3] (Evaluation of surface condition)
[0112] The coating liquid of the adhesive composition prepared in the examples and comparative examples was applied to the release surface of a release sheet (manufactured by LINTEC CORPORATION, product name "SP-PET381031") in which a silicone release agent layer was formed on one side of a polyethylene terephthalate film having a thickness of 38 μm at a coating speed of 1 m / min, and heated at 130° C. for 2 minutes to form an adhesive layer having a thickness of 25 μm on the release sheet.
[0113] The surface of the formed adhesive layer opposite to the release sheet was observed, and the surface condition was evaluated based on the following criteria.
[0114] ○: No streaks were observed.
[0115] △: Streaks were observed in a part.
[0116] ×: Streaks were observed on the entire surface, or the adhesive layer was not sufficiently cured.
[0117] [Test Example 4] (Evaluation of pot life)
[0118] The coating liquid of the adhesive composition prepared in the embodiment and the comparative example was left to stand for 1 hour at room temperature of 23°C and humidity of 50%RH. Afterwards, the viscosity (mPa·s) of the coating liquid was measured using a B-type viscometer (manufactured by fungilab, product name "VISCOLEAD") at a measuring temperature of 23°C, a rotating shaft of L2, and a rotation speed of 60 rpm. Then, the pot life of the coating liquid was evaluated based on the following criteria. The results are shown in Table 1.
[0119] ○: The viscosity is 6000 mPa·s or less.
[0120] △: The viscosity is greater than 6000 mPa·s and less than 10000 mPa·s.
[0121] ×: The viscosity is higher than 10,000 mPa·s, or the adhesive composition is gelled.
[0122] [Test Example 5] (Measurement of gel fraction)
[0123] The coating liquid of the adhesive composition prepared in the Examples and Comparative Examples was applied at a coating speed of 1 m / min to the release surface of a release sheet (manufactured by LINTEC CORPORATION, product name "SP-PET381031") formed on one side of a polyethylene terephthalate film having a thickness of 38 μm, and heated at 130° C. for 2 minutes to form an adhesive layer having a thickness of 25 μm on the release sheet. The release surface of a release sheet (manufactured by LINTEC CORPORATION, product name "SP-PET382150") formed on one side of a polyethylene terephthalate film having a thickness of 38 μm was attached to the surface of the formed adhesive layer opposite to the release sheet, thereby obtaining a sample for measuring gel fraction.
[0124] Then, 0.2 g of the adhesive layer in the sample for measuring gel fraction was wrapped in a polyester mesh (mesh size 200), and the mass was weighed with a precision balance, and the mass of the adhesive layer itself was calculated by subtracting the mass of the mesh alone. The mass at this time was set as M1.
[0125] Next, the adhesive layer wrapped in the polyester mesh was immersed in ethyl acetate at room temperature (23°C) for 48 hours. After that, the adhesive layer was taken out and heated and dried at 120°C for 2 hours. After drying, the mass was weighed with a precision balance, and the mass of the adhesive layer itself was calculated by subtracting the mass of the mesh alone. The mass at this time was set as M2.
[0126] The gel fraction (%) of the pressure-sensitive adhesive layer was calculated by the following calculation formula using the values of M1 and M2 calculated as described above.
[0127] (M2 / M1)×100=Gel fraction (%)
[0128] In addition, the details of the abbreviations and the like described in Table 1 are as follows.
[0129] [Crosslinking agent]
[0130] TAKENATE D-101E: Trimethylolpropane-modified toluene diisocyanate (manufactured by TOYOCHEM CO., LTD., product name "TAKENATE D-101E")
[0131] D-370N: Pentamethylene diisocyanate isocyanurate (manufactured by Mitsui Chemicals, Inc., product name "STABiO D-370N")
[0132] HX: Hexamethylene diisocyanate isocyanurate (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HX")
[0133] D-376N: Pentamethylene diisocyanate-based isocyanurate (allophonate mixture, manufactured by Mitsui Chemicals, Inc., product name "STABiO D-376N")
[0134] TSA100: Hexamethylene diisocyanate-based isocyanurate (allophenate mixture, manufactured by Asahi Kasei Corporation, product name "DURANATE TSA-100")
[0135] TSE100: Hexamethylene diisocyanate-based isocyanurate (allophenate mixture, manufactured by Asahi Kasei Corporation, product name "DURANATE TSE-100")
[0136] [Blockers]
[0137] acac: Acetylacetone (manufactured by FUJIFILM Wako Pure Chemical Corporation, product name "ACETYLACETONE")
[0138] AAEM: 2-acetoacetoxyethyl methacrylate (manufactured by Mitsubishi Chemical Corporation)
[0139] [Table 1]
[0140]
[0141] As can be seen from Table 1, the workpiece processing sheets obtained in Examples have excellent environmental performance and almost no odor generation problem. In addition, the workpiece processing sheets obtained in Examples have a sufficiently long pot life of the coating liquid and have an adhesive layer with an excellent surface state.
[0142] Industrial Applicability
[0143] The workpiece processing sheet of the present invention can be suitably used for processing a workpiece such as a semiconductor wafer.
Claims
1. A workpiece processing sheet comprising a substrate and an adhesive layer laminated on one side of the substrate, characterized in that: The adhesive layer is composed of an acrylic adhesive, and the acrylic adhesive is formed of a solvent-free adhesive composition containing an inhibitor that delays a cross-linking reaction.
2. The workpiece processing sheet according to claim 1, characterized in that: The solvent-free adhesive composition contains an acrylic oligomer.
3. The workpiece processing sheet according to claim 2, characterized in that: The weight average molecular weight of the acrylic oligomer is 1,000 or more and 40,000 or less.
4. The workpiece processing sheet according to claim 1, characterized in that: The blocker is a compound having a diketone skeleton.
5. The workpiece processing sheet according to claim 1, characterized in that: The content of the retarder in the solvent-free adhesive composition is 2 mass % or more and 30 mass % or less.
6. The workpiece processing sheet according to claim 1, characterized in that: The solvent-free adhesive composition contains a cross-linking agent.
7. The workpiece processing sheet according to claim 1, characterized in that: The solvent-free adhesive composition contains a catalyst for accelerating the cross-linking reaction.
8. A manufacturing method, which is a manufacturing method of the workpiece processing sheet according to claim 1, characterized in that: The manufacturing method comprises: a coating step of coating the solvent-free adhesive composition on one side of the substrate or the process sheet to form a coating film; and The heating step heats the coating film to form the adhesive layer in which the coating film is cured.
Citation Information
Patent Citations
Re-peelable pressure-sensitive adhesive composition and pressure-sensitive adhesive tape or sheet
JP2010106283A